Sistema de asistencia de reparaciones por soldadura adscrito a departamento de mantenimiento de maquinaria amarilla. (2024)
In this work we sought to propose a welding repair assistance system that can be implemented as an area attached to an existing maintenance program in a company that works with yellow machinery. Different failures in this type of equipment were studied depending on their category and organization in a Pareto diagram. A defect study was carried out in the 20% of the most frequent cases to estimate the causes of the failures and investigate the most appropriate technological procedures for their recovery by welding. It is important to mention that the statistics obtained were used to make a projection of the estimated costs to carry out repairs to the machinery. On the other hand, a preventive maintenance program was analyzed to design the welding repair assistance system so that it operates in an integrated manner. With the actions proposed in the recovery of components, it is expected to improve and prolong their useful life, reducing the frequency of part replacement and the amount of waste.